A Schema-Based Robot Controller Complying With the Constraints of Biological Systems - Lagriffoul, Fabien (Frontiers in Neurorobotics, 2022)
This article reports on the early stages of conception of a robotic control system based on Piaget’s schemas theory. Beyond some initial experimental results, we question the scientific method used in developmental robotics, and argue that it is premature to abstract away the functional architecture of the brain when so little is known about its mechanisms. Instead, we advocate for applying a method similar to the method used in model-based cognitive science, which consists in selecting plausible models using computational and physiological constraints. Previous work on schema-based robotics is analyzed through the critical lens of the proposed method, and a minimal system designed using this method is presented.